1991
DOI: 10.1108/eb023290
|View full text |Cite
|
Sign up to set email alerts
|

Format Citation Patterns and Their Implications for Collection Development in Research Libraries

Abstract: In this time of rapidly increasing journal subscription costs and shrinking (or stable) acquisition budgets, it is imperative to acquire materials as effectively as possible. One method of doing this is to use citation analysis of the scholarly literature as a guideline. Citation analysis is the analysis of the references from a set of documents (such as an analysis of all of the citations from five years of College & Research Libraries or of all citations from geology dissertations at a university). Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
3
13
1
Order By: Relevance
“…While collection development choices should be primarily guided by localized knowledge of the particular institution's research needs, citation analyses of the broader discipline can inform library collection development, as noted in previous literature [13][14][15][16][17][18]. This study suggests several consequences for library collection development for sociological research, including selection, storage, and weeding of materials as well as serials/monograph budget allocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While collection development choices should be primarily guided by localized knowledge of the particular institution's research needs, citation analyses of the broader discipline can inform library collection development, as noted in previous literature [13][14][15][16][17][18]. This study suggests several consequences for library collection development for sociological research, including selection, storage, and weeding of materials as well as serials/monograph budget allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that monographs receive a greater proportion of citations than journal articles in the sociological literature [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Michael Bowman's review of citation studies in all three areas includes only one on linguistics. 10 Within the humanities, the subject category in which linguistics has most o en been placed, a large number of citation analyses have focused on the field of literary scholarship. [11][12][13][14][15][16] In addition to literary studies, John M. Cullars has examined the citation characteristics of monographs in the fine arts and philosophy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Broadus (1977), librarians have long used citation analysis for collection building and management. Similarly, Bowman (1991) argued that citation patterns could be used as one method for deciding the suitability of specific items for inclusion in a library's collection. Of special interest to Bowman were the formats cited (for example, books and journals), languages of items cited, and the age of items cited.…”
Section: Literature Reviewmentioning
confidence: 99%